2018
DOI: 10.2196/jmir.7737
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of a Motivational Interview Delivered by a Robot: Qualitative Study

Abstract: BackgroundMotivational interviewing is an effective intervention for supporting behavior change but traditionally depends on face-to-face dialogue with a human counselor. This study addressed a key challenge for the goal of developing social robotic motivational interviewers: creating an interview protocol, within the constraints of current artificial intelligence, which participants will find engaging and helpful.ObjectiveThe aim of this study was to explore participants’ qualitative experiences of a motivati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 37 publications
2
74
0
Order By: Relevance
“…Finally, there are also clear benefits of having a virtual or robotic therapist that is always accessible, has endless amounts of time and patience, never forgets what a patient has said, and does not judge [63,64], thus potentially offering a service that is highly reliable and particularly well-suited to certain patient populations. If integrated into a scaled provision of services, AI-enabled applications could provide support for mild cases of depression and other nonacute conditions [65], therefore helping health professionals to devote more time to the most severe cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there are also clear benefits of having a virtual or robotic therapist that is always accessible, has endless amounts of time and patience, never forgets what a patient has said, and does not judge [63,64], thus potentially offering a service that is highly reliable and particularly well-suited to certain patient populations. If integrated into a scaled provision of services, AI-enabled applications could provide support for mild cases of depression and other nonacute conditions [65], therefore helping health professionals to devote more time to the most severe cases.…”
Section: Resultsmentioning
confidence: 99%
“…Ideas around embodied AI are culturally and historically shaped. Whether providing motivational interviews in therapy [64], acting as embodied conversational agents for mental disorders [47], or working with populations with intellectual disabilities [90], discussion of embodied AI often turns to worries surrounding the limits of human control over technology. Conjuring images of the Terminator or other depictions of the nonhuman in science fiction or cinema, such tools can carry with them negative or scary associations that bring the issue of trust in medical practice into new light [6].…”
Section: Discussionmentioning
confidence: 99%
“…Our review revealed that 6 of the studies used clinical care staff to observe and measure outcomes related to mood and mood-related behavioral changes, 3 used self-report data [42,43,48], and 3 had researchers use tracking sheets [44,46,50] to report on mood and mental health outcomes. These methods may be an artifact of the populations studied, due to the majority of studies involving persons with cognitive issues who would make self-report challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Our study highlights the possibility of applying a sequential approach to constructing an automated motivational interview with MI skills to integrate both technical and relational components. Previous research has remained rather vague in explicating the relational component or has excluded it in its entirety owing to technological issues (ie, [1,12]). It is important that the MI counsellor uses interactional skills strategically to convey an empathic understanding [15].…”
Section: Discussionmentioning
confidence: 99%